Analisis Performansi Media Penyimpanan Data IP Camera Menggunakan Metode PPDIOO - Ayu Vidiya Wati; I Putu Hariyadi; Lalu Zazuli Azhar Mardedi (Jurnal Teknologi Informasi dan Multimedia, 2026)
Closed-Circuit Television (CCTV) systems operating continuously for 24 hours generate large volumes of video data, requiring storage media that provide stable performance and high reliabil-ity under continuous workloads. Although dedicated CCTV hard disk drives (HDDs) are widely deployed in surveillance systems, studies that directly compare their performance with standard Personal Computer (PC) HDDs in Internet Protocol (IP) Camera-based surveillance environments remain limited. This study aims to analyze and compare the performance of these two storage media using the Prepare, Plan, Design, Implement, Operate, and Optimize (PPDIOO) methodology. The experimental setup consisted of 10 Hikvision IP cameras with 1080p resolution connected to a Network Video Recorder (NVR). Performance evaluation was conducted based on sequential write speed, recording stability, frame drops, operating temperature, and storage capacity utilization. Testing was performed using CrystalDiskMark, iVMS-4200, Hik-Connect, and Hard Disk Senti-nel. The results demonstrate that the dedicated CCTV HDD provides more stable performance than the standard PC HDD. The CCTV HDD achieved a sequential write speed of 206.67–207.00 MB/s, while the PC HDD reached 205.10–205.85 MB/s. During continuous recording, the CCTV HDD ex-perienced only one dropped frame, whereas the PC HDD recorded approximately four to six dropped frames. In addition, the CCTV HDD maintained a more stable operating temperature throughout the 24-hour recording period. Storage capacity analysis indicated that a surveillance system with 10 cameras operating at a bitrate of 4 Mbps requires approximately 422 GB of stor-age per day or 11.6 TB for one month. The main contribution of this study is a comprehensive per-formance evaluation of dedicated CCTV storage compared with conventional PC HDDs, providing practical recommendations for selecting reliable storage media in IP Camera-based surveillance systems.